Uncovering the link between incidental physical activity and inhibition of automatic responses in aging. An ERP study - Sanchez-Lopez, Javier; Silva-Pereyra, Juan; Sánchez-Moguel, Sergio Manuel; Alatorre-Cruz, Graciela Catalina; González-López, Mauricio; Sigg-Alonso, Jorge A; Pérez-Figueroa, Mariana; Fernández, Thalía (Frontiers in Aging Neuroscience, 2025)
The concept of cognitive reserve explains how the brain maintains function despite age-related changes or neuropathological damage. Factors such as education, cognitive stimulation, and physical activity contribute to strengthening this reserve. While research has highlighted the benefits of structured exercise, less attention has been given to the impact of incidental physical activity (IPA) everyday, unplanned movements like walking or household chores. This study examined the relationship between IPA and the inhibition of automatic responses, a key executive function that tends to decline with age. A total of 59 healthy older adults (mean age = 67; standard deviation = 4.95; range = 60–82; 35 females) were assessed and divided into two groups based on their IPA levels, measured using the Yale Physical Activity Survey. They then completed a Counting-Stroop task, designed to assess inhibitory control, while event-related potentials (ERPs) were recorded to measure brain activity. Behavioral results confirmed the Stroop effect in both groups, with similar patterns observed overall and only one between-group difference during the incongruent condition. ERP analyses revealed greater late negativity as a result of the differences between conditions (1,050–1,200 ms) during the counting-Stroop task in the high-IPA group, suggesting more effective late-stage inhibitory processing post-execution likely related to re-evaluation and resolution of the conflict, while the low-IPA group lacked this effect. Furthermore, distinct neural activity patterns between the conditions were observed for each group as well. The high-IPA group showed differences between congruent and incongruent conditions between 300 and 500 ms, suggesting earlier conflict monitoring, while the low-IPA group exhibited significant differences over frontal areas in the 500–700 ms window, likely suggesting a different strategy for resolving interference. These findings suggest that IPA may enhance executive function by mainly supporting the later stages of inhibitory control mechanisms at a neural level, even when behavioral performance remains comparable. Given its accessibility, IPA may be a valuable strategy to maintain cognitive reserve and promote healthy aging. Future research is necessary to further explore the relationship between IPA and cognition in the context of cognitive reserve.